Previous concrete as one of the technology to overcome the puddle. (March 2018) - Agung Putra Handana, M; Karolina, Rahmi; Syahputra, Eko; Zulfikar
Abstract: Some construction waste has been utilized as a material in certain concrete compositions for engineering building materials. One is a concrete that has been removed after testing at a laboratory called recycle concrete. Disposed concrete, crushed and filtered with filter number 50; 37.5; 19; 9.5; and 4.75 mm are subsequently converted into rough aggregate materials in the manufacture of pervious concrete to be tested for compressive strength and infiltration velocity to water. Pervious concrete test specimens in the form of cylinders with dimensions (15 x 30) cm and plate-shaped with dimension (100 x 100 x 10) cm with the quality plan Fc ' = 15 MPa at age 28 days. The research methodology consisted of testing of wear, test object preparation, periodic maintenance, visual inspection, compressive strength testing, and infiltration rate of specimens against water (based on ASTM C1701). Treatment of specimens by spraying periodically before the test time. From the results of the Los Angeles wear test, it appears that recycled aggregate has an average wear rate of 20.88% (based on SNI 03-2417-1991) on the Los Angeles test) and the visual test on the specimen is appropriate (based on SNI 03 -0691-1996 on paving block) as the basis for testing the specimens. The largest compressive strength was found in pervious concrete with 9.5 mm graded aggregates of 5.89 MPa, while the smallest compressive strength of 50 mm gradation was 2.15 MPa and had a compressive strength of 28% of pervious concrete compressive strength on generally (based on SNI 03-6805-2002). The fastest infiltration speed occurs in 50 mm pervious gradient concrete at 4.52 inc / hr and is late in 9.5 mm grading of 2.068 inc / hr or an inflation rate inflation rate of 54.25% for gradation of 9.5 mm to 50 mm gradation, So that in accordance with the purpose of pervious concrete use, concrete that can drain water to the bottom layer